Nightmare of the iguana - Vernon, Ursula (Vernon, Ursula. Dragonbreath, 2013)
Wendell the iguana's dreams are all nightmares and a Dream Wasp wants him as a host for her eggs--so, with Great-grandfather Dragonbreath's help, Danny the dragon and Suki the salamander enter Wendell's dreams to try and defeat the wasp.